Secondary School Pupils' Mental Wellbeing Is Associated with Belonging to a Perceived Minority and Experiencing Discrimination - Pinja Kokkonen; Christina Athanasopoulou; Helena Leino-Kilpi; Evanthia Sakellari (MDPI AG, 2021)
Adolescents' mental health is a global issue and there is a growing interest in tackling mental health in schools. The study aimed to assess secondary school pupils' mental wellbeing and the factors related to their mental wellbeing (sociodemographic characteristics, perception of belonging to a minority, and discrimination). Data were collected from 12-17-year-old pupils of a Finnish secondary school via an online questionnaire. Data were analyzed with descriptive statistics and ANOVA for group comparisons. Participants' (Ν = 114) mental wellbeing scores were above average (47.5, max. 70). Worse family relations were independently associated with worse mental wellbeing. Additionally, significantly lower scores on mental wellbeing were found among pupils who thought they belonged to a minority due to appearance, sexual orientation, and/or chronic disease. Participants who had experienced discrimination had significantly lower mental wellbeing scores in comparison to those who never had such an experience. In conclusion, mental health promotion interventions which promote good family relations should be targeting different youth groups in order to address their specific needs. Thus, screening programs which identify pupils who are at risk or belong to minority groups are needed, in order to direct them to proper services when needed and/or implement mental health promotion interventions accordingly.